ANALISIS KETERAMPILAN MENULIS PUISI MELALUI MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS IV SDN PANDEANLAMPER O3 - Zulfa, Iffa Chasanah; Purnamasari, Veryliana; Murniati, Ngurah Ayu Nyoman; Saputro, Susilo Adi (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This research aims to describe poetry writing skills through the PBL model and describe the application of the PBL model in Indonesian language learning for class IV students at SDN Pandeanlamper 03 Semarang. Qualitative descriptive research using observation, interviews and documentation methods. The results of this research and discussion explain that the PBL (Problem Based Learning) learning model in Indonesian language learning for class IV students looks active, enthusiastic and enthusiastic in participating in learning. This learning model invites students to think critically to write poetry. Then, writing students' poetry skills through the PBL model with the help of pictures about the natural appearance of Raja Ampat is good with a percentage of 77.40% of students who are able to find ideas and process vocabulary, but there are some students who still feel confused in finding ideas and looking for vocabulary. the right way to compose poetry. Therefore, students' poetry writing skills through the Problem Based Learning model can help students develop imagination, find the right ideas and vocabulary.